1982
DOI: 10.1111/j.1365-2389.1982.tb01794.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in soil aggregate water stability induced by wetting and drying cycles in non‐saturated soil

Abstract: Wetting and drying of remoulded soil resulted in water stable aggregation. The greatest proportions of water stable aggregates arose from wetting and drying in the -1 to -100 kPa range of matric water potential. The effect occurred with sterile and non-sterile soil. but the proportion ofwater stable aggregates was less with sterile soil.The application of wetting and drying cycles in the laboratory to non-tilled soil resulted in a steady decrease in the proportion of water stable aggregates. With tilled soil, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
6

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(68 citation statements)
references
References 19 publications
2
59
1
6
Order By: Relevance
“…The nature of deformation by tillage will determine the characteristics of failure zones and the resulting aggregate size distribution, porosity, pore size distribution, and pore continuity, as well as the variation in these characteristics of structural form ,!\,ith depth. When tillage leads to an increase in the extent of failure zones, reduced stability is also observed (Utomo and Dexter, 1982). The propagation through soil of different stresses arising from tillage equipment and the resulting defonnation of the soil matrix are reviewed in greater detail by Koolen and Kuipers (1983) and Hettiaratchi (1988).…”
Section: Deformation By Shearing Compression and Tensile Stressesmentioning
confidence: 97%
“…The nature of deformation by tillage will determine the characteristics of failure zones and the resulting aggregate size distribution, porosity, pore size distribution, and pore continuity, as well as the variation in these characteristics of structural form ,!\,ith depth. When tillage leads to an increase in the extent of failure zones, reduced stability is also observed (Utomo and Dexter, 1982). The propagation through soil of different stresses arising from tillage equipment and the resulting defonnation of the soil matrix are reviewed in greater detail by Koolen and Kuipers (1983) and Hettiaratchi (1988).…”
Section: Deformation By Shearing Compression and Tensile Stressesmentioning
confidence: 97%
“…In newly remolded aggregates, Utomo and Dexter (1982) showed that wetting and drying increased the percentage of water-stable aggregates two-to fourfold. Nevertheless, Hindell et al (1997b) reported opposite results for initially air-dried casts and uningested soil.…”
Section: Role Of Organic Mattermentioning
confidence: 99%
“…Finally, the different soil moisture regime resulting from irrigation can also affect soil structure by reducing the occurrence of dry-wet cycles. Although dry-wet cycles in aggregated soils have been shown to have detrimental effects on aggregation (e.g., Utomo and Dexter, 1982), the overall impact of dry-wet cycles on soil structure depends on several soil factors ) and appears to be only short term (Denef et al, 2001).…”
mentioning
confidence: 99%